Research Trends on Mathematical Problem-Solving Ability Analysis From 2015 to 2024: Bibliometric Analysis - Yusuf Devan Nr; Angraini, Lilis Marina; Sadiq, Hamidi (International Journal of Applied Learning and Research in Algebra, 2025)
The purpose of this bibliometric analysis is to identify opportunities and trends in research related to mathematical problem-solving abilities on the topic of functions. This study uses a bibliometric method by collecting data from articles published between 2015 and 2024 through Google Scholar using the Publish or Perish software, with a total of 1,000 journal articles. Bibliometrics is used to provide a structural overview of a particular research era, containing the necessary information to analyze publications in fields relevant to the researcher’s focus. The findings of this study show that from 2015 to 2024, there were 994 articles related to mathematical problem-solving abilities on the topic of functions. The highest number of publications occurred in 2020, with a total of 177 publications, while the lowest was in 2024, with only 21 publications, based on analysis using the VOSviewer software. Variables related to mathematical problem-solving abilities on the topic of functions that present opportunities and novelty for future research include critical thinking ability, high school, mathematical problem solving, PBL (problem-based learning), development, grade VIII, analysis, and learning. These variables have not been widely explored by other researchers, indicating the potential for innovation and further development by future researchers.